IMPLEMENTASI KEBIJAKAN PROGRAM PEMBANGUNAN SARANA DAN PRASARANA PERAWATAN PARA PENYANDANG CACAT DAN TRAUMA DI KOTA SURAKARTA (Studi Kasus Di Dinas Sosial Tenaga Kerja Dan Transmigrasi Kota Surakarta) - Joko Suranto, Claudia Shabet Lailasari, Winarti & (Transformasi, 2017)
The standard and target group of the program was good because it is given to peoplewith disabilities who are poor and still productive, this program has not been able to meetthroughout the disability who need help it is evident that from 273 disabled people only 125people with disabilities who helped by this programs. Human resources were well and effectivebecause it includes all stakeholders, from the city bureaucrat to the lowest bureaucratic orderi.e. village. Budgetary resources have not been sufficient for all of the recipients in Surakarta.Facilities or infrastructure in the implementation of the program is already good because it suitsthe needs of the disabled. Communication between the implementing organization andcommunication is done by other government agencies are already good but communication withprivate institutions is very less. The economic environment, social and political policy is givenon the disabled which have low economic conditions or can be found on the poor citizens. Socialconditions showed that the target group not yet peace. Managing the disposition has a goodcommitment in assisting the implementation of the development programme infrastructure caredisabilities and trauma.Key words: policy implementation, construction of infrastructure, the disabled and trauma